Orchestration in learning technology research: evaluation of a conceptual framework - Luis P. Prieto; Yannis Dimitriadis; Juan I. Asensio-Pérez; Chee-Kit Looi (Association for Learning Technology, 2015)
The term 'orchestrating learning' is being used increasingly often, referring to the coordination activities performed while applying learning technologies to authentic settings. However, there is little consensus about how this notion should be conceptualised, and what aspects it entails. In this paper, a conceptual framework for orchestration-related research is evaluated by an international panel of learning technology experts. The results of this evaluation show that the framework is complete and understandable, and it is particularly useful as an integrative list of aspects to consider when designing and evaluating learning technologies. To illustrate a way in which the framework can be used to help researchers structure their classroom innovation evaluations, an example is presented that follows the adoption of the framework by a group of researchers in Singapore. Finally, a new evolved version of the framework is presented, taking into account the evaluation feedback.